2019
DOI: 10.1177/2309499019836160
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the CT scan in the evaluation and treatment of nondisplaced femoral neck fractures in the elderly

Abstract: Background: The management of nondisplaced femoral neck fractures (FNFs) has evolved, with emphasis in radiographic features such as posterior displacement. However, the role of advanced imaging in this scenario is still not well defined. Therefore, our objective is to assess the impact of a computed tomography scan (CT) on interobserver agreement (IA) of fracture classification, posterior tilt measurement, and treatment decisions in nondisplaced FNF in elderly patients. Methods: Eleven patients with a nondisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Currently, the optimal treatment for NDFNFs is still controversial because few RCTs with a high level of evidence were conducted. The major considerations include postoperative function, complications, reoperation rate, and total cost [ 26 , 34 , 45 47 ]. You et al [ 48 ] indicated that internal fixation was associated with mild pain and better patient satisfaction but was associated with a high re-operation rate (20%).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the optimal treatment for NDFNFs is still controversial because few RCTs with a high level of evidence were conducted. The major considerations include postoperative function, complications, reoperation rate, and total cost [ 26 , 34 , 45 47 ]. You et al [ 48 ] indicated that internal fixation was associated with mild pain and better patient satisfaction but was associated with a high re-operation rate (20%).…”
Section: Resultsmentioning
confidence: 99%
“…It improves accuracy in fracture classification, which helps in selecting the best treatment for patients with fractures. 16 CT can scan the transverse and longitudinal sections, which is more conducive to discovering fractures and helps in diagnosing occult femoral neck fracture or microfractures to avoid missed diagnosis or the wrong choice of surgical procedure. 31 , 32 A better understanding of the status of femoral neck fractures is essential for preoperative evaluation and is associated with a better surgical and clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Computed tomography (CT) is a diagnosis tool for femoral neck fractures and provides preoperative evaluation for helping to choose the best treatment and provide better surgical and clinical outcomes. 16 , 17 Quantitative analysis of bone-texture features from CT scans has been actively applied to evaluate the status, quality, or microarchitecture of bones. 18 Park et al demonstrated the value of CT in prediction of avascular necrosis after femoral neck fracture.…”
Section: Introductionmentioning
confidence: 99%
“…However, the measurement of posterior tilt by X-ray lateral radiographs is limited by non-standard position, anatomical variation, bone density and image quality. Zamora and colleagues [14] proposed that CT axial oblique plane can make up for the limitations of X-ray measurement, but this measurement method only uses one axial oblique 2D tomographic CT image, which is still affected by selection bias and hip position. In this study, the measurement of the posterior tilt is an improvement of Wu and colleagues [15] measurement method, because there is still a certain error in the establishment of the center of the femoral head at four points.…”
Section: Discussionmentioning
confidence: 99%